An integrated marketing communications campaign for the Robotic Surgery of St. Luke's Medical Center, Global City - Padua, Jesusa Angela A. (Animo Repository, 2016)
This study and campaign intends to propose an integrated marketing campaign for the Robotic Surgery service of St. Lukes Global City. Five years after this innovation was brought to the country, there have been 500 procedures performed despite limited efforts of marketing it to the public. The study looked into the growth rate of the Minimally Invasive and Robotic Surgery Center and expects a continuous annual increase despite its apparent lack of exposure. The Researcher believes that with the use of different communication channels, the awareness for this type of alternative to conventional open surgery and laparoscopic surgery may be amplified. There is a possibility of maximizing the capacity of the Center once awareness is addressed. Moreover, there is a part of the market that is constantly looking for options in bettering their condition. This yielded pertinent information through a number of in-depth interviews. Furthermore, this presented various perceptions about the institution, its image, and services that backs-up recommendations. In-depth interviews were conducted because it is an open-ended, discovery-oriented method to obtain detailed information. Information dissemination is the main key in dealing with the issue on lack of awareness. The researcher proposes a campaign that will make use of events, placements of print advertisements, digital efforts, in-store promotional materials, and features on broadsheets, magazines, and TV. At the end of the year-long campaign, the effectiveness of each medium will be evaluated so as to determine which provided notable effect. This may be a piqued interest, a desire to avail of the service, or a direct action or response that translates to a successful campaign.